2023
DOI: 10.1002/jper.22-0716
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of titanium release following non‐surgical peri‐implantitis treatment: A randomized clinical trial

Abstract: BackgroundPeri‐implantitis is a frequent finding. Initial treatment involves non‐surgical debridement of the implant surface. Recent studies have found a correlation between titanium (Ti) particle release and peri‐implantitis, yet there is a dearth of information regarding the effect of various non‐surgical instrumentation on particle release or peri‐implantitis resolution.Materials and MethodsPatients with peri‐implantitis were recruited for a randomized, blinded, parallel‐group clinical trial. The implants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Moreover, recent studies have reported that micromotion and fretting wear can break down the Ti passive film, exposing Ti to the action of the surrounding complex media and resulting in the generation of large amounts of debris and continuous release of Ti ions [ 18 ]. A correlation was observed between the release of Ti particles and peri-implantitis [ 19 ]. Micromotion in the IACs can be a risk factor for peri-implantitis in terms of both bacterial and Ti-ion leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have reported that micromotion and fretting wear can break down the Ti passive film, exposing Ti to the action of the surrounding complex media and resulting in the generation of large amounts of debris and continuous release of Ti ions [ 18 ]. A correlation was observed between the release of Ti particles and peri-implantitis [ 19 ]. Micromotion in the IACs can be a risk factor for peri-implantitis in terms of both bacterial and Ti-ion leakage.…”
Section: Discussionmentioning
confidence: 99%
“…While debris from the implant itself may be released to the peri-implant bone, such debris may also be produced at the interface between the prosthesis and the implant or between the implant and the transmucosal abutments [13]. In fact, numerous studies have found titanium particles released from the implants in the surrounding tissues [14][15][16][17][18][19][20][21]. Within this debate, the activation of NLRP3, specifically, may help in finding a biologically plausible explanation for the differences between periodontitis and peri-implantitis.…”
Section: Introductionmentioning
confidence: 99%
“…Згідно результатів отриманих Daubert D. та колегами, рівень розчиненого титану в тканинах, що оточують внутрішньокісткову опору з ознаками периімплантиту, є чинником, що визначає статус периімплантатного ураження та модифікатором мікробіому, корелюючи із його специфічними сигнатурами [32]. Хоча в пізнішому лабораторному дослідженні від 2022 року було встановлено, що ефект релізингу іонів титану значимо не впливає на процес формування біоплівки чи бактеріальну реколонізацію поверхні опори після її очистки [33]. З іншої сторони було констатовано, що саме бактеріальна корозія, включаючи фактор товщини біоплівки, асоційованої з розвитком периімплантиту, провокує виражене зростання вивільнення іонів титану із поверхні імплантату [9,34].…”
unclassified